Perencanaan dan Pelaksanaan Pembelajaran yang Efektif - Wita Marheni; Patricia Wira Lestari; Lisa Sababalat; Lisna Novalia (Pusat Riset dan Inovasi Nasional, 2025)
Learning planning is a learning activity or activity that is structured through planning. The aim of this planning is to achieve the expected results and even produce potential students. Therefore, before carrying out learning, teachers must prepare a learning plan. An educator must have a learning plan because it is very important and even becomes a guideline and standard in achieving goals. The aim of this research is to find out how the implementation of learning planning affects teacher performance and the learning process. This research uses a qualitative descriptive research method. And good learning planning will make the implementation of learning run effectively and well.